Tipping paper with low heavy metal content and preparation method thereof

By setting a base material layer, a modified silicon carbide layer and a protective layer on the coupling paper, the problem of heavy metal pollution in traditional coupling paper is solved, and packaging materials with low heavy metal content, environmentally friendly and safe content are achieved, ensuring food safety and durability of packaging materials.

CN119593259APending Publication Date: 2025-03-11ZHEJIANG MANDE NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411957610.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Traditional loading paper may introduce harmful heavy metals such as lead, cadmium, and mercury during the production process, affecting food safety and human health.

Method used

The modified silicon carbide solution is uniformly applied to the paper base layer, the modified silicon carbide layer and the protective layer provided from the inside out, and the modified silicon carbide solution is uniformly applied to the paper base surface by ultrasonic treatment to form a silicon carbide coating with good stability, and epoxy resin coating is applied to the surface as the protective layer.

Benefits of technology

Effectively reduce the heavy metal content in the loading paper, avoid heavy metal migration, ensure food safety, and improve the chemical stability and thermal stability of packaging materials and extend service life.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of tipping paper, and provides tipping paper with low heavy metal content and a preparation method thereof. The tipping paper comprises a base material layer, a modified silicon carbide layer and a protective layer which are arranged from inside to outside, the preparation method comprises the following steps: S100, pretreating a cellulose paper base material to obtain a paper base; s200, under ultrasonic treatment, the paper base is soaked in a modified silicon carbide layer solution, and the tipping paper containing the modified silicon carbide layer is obtained; and S300, the surface of the tipping paper containing the modified titanium carbide layer is coated with a protective coating, and the low-heavy-metal-content tipping paper is obtained. By additionally arranging the modified silicon carbide layer and the protective layer, the potential risk of harmful heavy metals such as lead, cadmium and mercury in a traditional packaging material is avoided, meanwhile, the safety, stability and durability of the tipping paper are improved, and the environment-friendly advantage is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of tipping paper, and in particular to a tipping paper with low heavy metal content and a preparation method thereof. Background Art

[0002] In the modern packaging industry, as consumers' requirements for food safety and environmental protection continue to increase, packaging materials with low heavy metal content have become an important issue that needs to be solved urgently. Traditional tipping paper materials often use chemical components containing heavy metals, which may introduce harmful substances such as lead, cadmium, and mercury during the production process, which will not only affect the safety of the product, but also may cause potential harm to human health. Especially in the field of food packaging, excessive heavy metal content will cause toxic substances to migrate into food, thus posing a threat to consumer health.

[0003] Therefore, how to develop a tipping paper with low heavy metal content, environmental protection and safety has become a key issue that needs to be urgently solved in the industry. Summary of the invention

[0004] Therefore, the present invention provides a low heavy metal content plugging paper and a preparation method thereof, aiming to solve the problem of heavy metal pollution introduced into traditional plugging paper during the production process. The plugging paper of the present invention comprises a base material layer, a modified silicon carbide layer and a protective layer arranged from the inside to the outside, and the modified silicon carbide layer is ultrasonically treated to uniformly apply a modified silicon carbide solution to the surface of the paper base to form a silicon carbide coating with good stability. The coating not only avoids heavy metals such as lead, cadmium, mercury and the like that may be contained in traditional packaging materials, but also has excellent chemical stability and thermal stability; the protective layer adopts epoxy resin coating, which can provide additional protection for the plugging paper and prevent the external environment from corroding the packaging material.

[0005] In order to solve the above problems, the first object of the present invention is to provide a method for preparing a plugging paper with low heavy metal content;

[0006] The second object of the present invention is to provide a tipping paper with low heavy metal content;

[0007] To achieve the first objective of the present invention, the present invention provides a low-heavy metal content plugging paper and a preparation method thereof, wherein the plugging paper comprises a substrate layer, a modified silicon carbide layer, and a protective layer arranged from the inside to the outside; the preparation method comprises: S100, pre-treating a cellulose paper substrate to obtain a paper substrate; S200, soaking the paper substrate in a modified silicon carbide layer solution under ultrasonic treatment to obtain a plugging paper containing a modified silicon carbide layer; S300, coating a protective coating on the surface of the plugging paper containing a modified titanium carbide layer to obtain a low-heavy metal content plugging paper; wherein the modified silicon carbide solution is N-doped carbon quantum dot-silicon carbide.

[0008] In a technical scheme of the present invention, the modified silicon carbide solution adopts the following steps: S211, dissolving lignin and urea in deionized water to obtain a first mixed solution; S212, placing the first mixed solution into a reactor, heating the reaction at a temperature of 180-250°C for 4-8 hours, and cooling to room temperature to obtain an N-doped carbon quantum dot solution; S213, adding silicon carbide powder to the N-doped carbon quantum dot solution, heat-treating it under a nitrogen atmosphere, and cooling to room temperature to obtain an N-doped carbon quantum dot-silicon carbide composite material; S214, dissolving the N-doped carbon quantum dot-silicon carbide composite material in anhydrous ethanol to obtain a modified silicon carbide solution.

[0009] In one technical solution of the present invention, in step S211, the mass ratio of lignin to urea is 1:(0.05-0.1); and / or in step S213, the mass ratio of silicon carbide powder to N-doped carbon quantum dot solution is 1:(1-3); and / or in step S213, the temperature of heat treatment is between 1000-1600°C.

[0010] In a technical solution of the present invention, after step S214, the method further includes: S215, adding a dispersant to the modified silicon carbide solution; wherein the mass of the dispersant accounts for 0.5-3% of the mass of the modified silicon carbide, and the dispersant includes at least one of polyvinyl alcohol and sodium polyacrylate.

[0011] In one technical solution of the present invention, in step S100, the pretreatment includes cleaning treatment, surface modification treatment and drying treatment.

[0012] In one technical solution of the present invention, in step S200, the frequency of ultrasonic treatment is 20-40 kHz, and the power is 50-100 W.

[0013] In a technical solution of the present invention, in step S300, the protective coating is an epoxy resin coating, and the epoxy resin coating contains 20-30wt% of polyamide, 8-10wt% of sodium carboxymethyl cellulose and 6-8wt% of nylon.

[0014] In one technical solution of the present invention, the viscosity of the epoxy resin coating is between 100 and 500 cP.

[0015] In a technical solution of the present invention, the thickness of the substrate layer is between 50 and 150 μm; the thickness of the modified silicon carbide layer is between 1 and 5 μm; and the thickness of the protective layer is between 8 and 20 μm.

[0016] To achieve the second objective of the present invention, the present invention provides a low heavy metal content tipping paper prepared by using any one of the above technical solutions.

[0017] After adopting the technical solution of the present invention, the following technical effects can be achieved:

[0018] (1) By coating a modified silicon carbide layer on the substrate layer, the heavy metal content in the tipping paper is effectively reduced, and the migration of harmful heavy metals such as lead, cadmium, and mercury is avoided, thereby ensuring the safety of food packaging;

[0019] (2) The design of the modified silicon carbide layer and protective layer gives the tipping paper excellent chemical and thermal stability, greatly enhancing the durability of the packaging material and extending its service life;

[0020] (3) The modified silicon carbide solution uses natural organic matter such as lignin and urea as the main raw materials. No excessive harmful chemical reagents are used in the preparation process, which has good environmental protection. At the same time, the protective coating uses epoxy resin coating to improve the durability and oxidation resistance of the tipping paper and ensure its stability in different environments. DETAILED DESCRIPTION

[0022] The word “exemplary” is used exclusively herein to mean “serving as an example, example, or illustration.” Any embodiment described herein as “exemplary” is not necessarily to be construed as preferred or advantageous over other embodiments.

[0023] The term "and / or" herein is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the term "at least one" herein represents any combination of at least two of any one or more of a plurality of. For example, including at least one of A, B, and C can represent including any one or more elements selected from the set consisting of A, B, and C.

[0025] In addition, in order to better illustrate the present disclosure, numerous specific details are given in the following specific embodiments. It should be understood by those skilled in the art that the present disclosure can also be implemented without certain specific details. In some examples, methods, means, components and circuits well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present disclosure.

[0026] In the modern packaging industry, as consumers' requirements for food safety and environmental protection continue to increase, packaging materials with low heavy metal content have become an important issue that needs to be solved urgently. Traditional tipping paper materials often use chemical components containing heavy metals, which may introduce harmful substances such as lead, cadmium, and mercury during the production process, which will not only affect the safety of the product, but also may cause potential harm to human health. Especially in the field of food packaging, excessive heavy metal content will cause toxic substances to migrate into food, thus posing a threat to consumer health.

[0027] Therefore, how to develop a tipping paper with low heavy metal content, environmental protection and safety has become a key issue that needs to be urgently solved in the industry.

[0028] The plugging paper of the present application includes a base layer, a modified silicon carbide layer and a protective layer arranged from the inside to the outside. The base layer is immersed in a modified silicon carbide layer solution to form a layer of silicon carbide coating with good stability. The coating can effectively reduce the heavy metal content in the plugging paper, avoid the migration of harmful heavy metals such as lead, cadmium, and mercury that may exist in traditional materials, and ensure food safety. At the same time, it also has excellent chemical stability and thermal stability, and enhances the durability and protective performance of the packaging material; by coating the protective layer, additional protection is provided for the plugging paper, effectively preventing the external environment from corroding the packaging material, and further reducing the risk of heavy metal release, thereby ensuring the safety and environmental protection of the packaging material.

[0029] The preparation method of the present invention comprises the following steps:

[0030] S100, pretreating a cellulose paper substrate to obtain a paper base;

[0031] S200, soaking the paper base in a modified silicon carbide layer solution under ultrasonic treatment to obtain a tipping paper containing a modified silicon carbide layer;

[0032] S300, coating the protective coating on the surface of the plugging paper containing the modified titanium carbide layer to obtain the plugging paper with low heavy metal content.

[0033] Preferably, in step S100, the pretreatment includes cleaning, surface modification and drying, specifically including: cleaning the cellulose paper substrate with deionized water by immersion, and accelerating the cleaning process by drying equipment; to remove dust, oil, fat and other impurities on the surface of the paper base; using nitrogen plasma treatment to form nitrides and amino groups to increase the adhesion of the paper surface; finally, using hot air drying on the cleaned and surface modified paper base to remove moisture from the paper base and ensure the uniformity and stability of the paper base; thus, after the above pretreatment, the surface properties of the paper base are improved, laying the foundation for the subsequent coating of the modified silicon carbide layer and the protective layer.

[0034] Further, in step S200, the modified silicon carbide solution adopts the following steps:

[0035] S211, dissolving lignin and urea in deionized water to obtain a first mixed solution;

[0036] S212, placing the first mixed solution into a reactor, heating the reaction at a temperature of 180 to 250° C. for 4 to 8 hours, and cooling to room temperature to obtain an N-doped carbon quantum dot solution;

[0037] S213, adding silicon carbide powder to the N-doped carbon quantum dot solution, performing heat treatment under a nitrogen atmosphere, and cooling to room temperature to obtain an N-doped carbon quantum dot-silicon carbide composite material;

[0038] S214, dissolving the N-doped carbon quantum dot-silicon carbide composite material in anhydrous ethanol to obtain a modified silicon carbide solution.

[0039] Preferably, lignin and urea are first dissolved in deionized water to form a first mixed solution. Lignin is a natural polymer material rich in aromatic structure and has good carbon source characteristics; urea is a nitrogen-containing compound. At high temperature, the aromatic structure in the lignin molecule and the nitrogen source molecule in the urea will undergo a pyrolysis reaction. The first mixed solution is placed in a reactor and heated, and the nitrogen source in the urea will decompose, releasing nitrogen atoms or amino groups, which react with the carbon source in the lignin to form nitrogen-containing carbon quantum dots. Specifically, lignin is cracked into small molecular carbides at high temperature, and these small molecules are then polymerized into nanoscale carbon quantum dots; at the same time, the nitrogen element in the urea is embedded in the structure of the carbon quantum dots to form N-doped carbon quantum dots. After the nitrogen atoms enter the carbon quantum dots, they usually replace part of the carbon atoms or form a nitrogen heterocyclic structure with the carbon atoms. This not only improves the hydrophilicity and compatibility of the carbon quantum dots with the solvent, but also increases the surface active sites, thereby enhancing its adsorption capacity for other substances. N-doped carbon quantum dots have excellent thermal and chemical stability, and can significantly enhance the oxidation resistance, heat resistance and UV resistance of the modified silicon carbide solution, thereby improving the long-term stability and durability of the coating.

[0040] Furthermore, in step S211, the mass ratio of lignin to urea is 1:(0.05-0.1). At this ratio, the nitrogen element in urea can fully participate in the doping reaction of carbon quantum dots to form N-doped carbon quantum dots, while avoiding the introduction of excessive nitrogen sources, preventing side reactions or the formation of unnecessary nitrogen heterocyclic structures. Controlling the mass ratio of nitrogen sources can also effectively avoid the interference of excessive urea on the cracking and carbonization of lignin, ensuring that lignin is fully cracked into small molecular carbides, so that the carbon quantum dots finally formed have a better nanoscale structure and a higher specific surface area; it helps to improve the adsorption performance of carbon quantum dots and their affinity for other substances, and further enhance the antioxidant, heat resistance and UV resistance of the modified silicon carbide solution.

[0041] Preferably, by adding silicon carbide powder to the N-doped carbon quantum dot solution and performing heat treatment under a nitrogen atmosphere, silicon carbide and N-doped carbon quantum dots can be fully reacted to form an N-doped carbon quantum dot-silicon carbide composite material with stronger binding force. Silicon carbide can effectively block the migration of heavy metals and harmful substances. Through the composite of N-doped carbon quantum dots and silicon carbide, the sealing and shielding capabilities of the silicon carbide layer can be further enhanced, effectively preventing the migration of heavy metals or harmful substances that may exist in the packaging material, and ensuring the safety of food packaging; at the same time, the strengthening effect of N-doped carbon quantum dots on silicon carbide makes the modified silicon carbide coating have stronger antioxidant and UV resistance, thereby greatly extending the service life of the tipping paper and improving stability.

[0042] Furthermore, the mass ratio of silicon carbide powder to N-doped carbon quantum dot solution is 1:(1-3), which can ensure that silicon carbide and N-doped carbon quantum dots fully react during the heat treatment process to form a stable composite material. An appropriate amount of N-doped carbon quantum dots can enhance the dispersibility of silicon carbide powder and avoid its agglomeration in the solution, making the interaction between silicon carbide particles more uniform, ensuring the structural uniformity and stability of the composite material. In addition, this ratio helps to form a strong interaction force between silicon carbide and N-doped carbon quantum dots, avoiding mutual interference caused by excessive carbon quantum dots, so that the composite material can effectively exert the synergistic effect of the two. The heat treatment temperature is between 1000 and 1600°C. Through heat treatment, N-doped carbon quantum dots can form more active sites, improve their surface reactivity, thereby enhancing the adsorption capacity and functionality of the composite material. High-temperature heat treatment helps to remove solvents and impurities in the solution, further improve the purity of the material, and enhance its thermal stability and antioxidant properties.

[0043] Preferably, the composite material is dissolved in anhydrous ethanol, and the N-doped carbon quantum dots can be effectively dispersed in the solution evenly to obtain a modified silicon carbide solution, so as to ensure uniformity in the subsequent coating process and ensure the quality and effect of the final tipping paper surface coating; since the materials in the modified silicon carbide solution of the present application are derived from natural organic matter such as lignin and urea, and no excessive harmful chemical reagents are used in the preparation process, the prepared modified silicon carbide solution has good environmental protection.

[0044] Furthermore, after step S214, the method further includes: S215, adding a dispersant to the modified silicon carbide solution; wherein the mass of the dispersant accounts for 0.5-3% of the mass of the modified silicon carbide, and the dispersant includes at least one of polyvinyl alcohol and sodium polyacrylate.

[0045] Preferably, the introduction of the dispersant helps to improve the adhesion between the modified silicon carbide solution and the paper base surface, optimize the fluidity and stability of the solution, improve the adhesion and durability of the coating, avoid coating shedding or uneven coating, reduce the coating difficulties caused by excessive viscosity, and also help to avoid material waste during the coating process and improve production efficiency; polyvinyl alcohol and sodium polyacrylate can interact with the components in the modified silicon carbide solution to prevent precipitation and stratification of the components in the solution, and introduce more active sites, which helps to combine the modified silicon carbide material with other components, thereby improving the performance of the final coating.

[0046] Preferably, in step S200, the frequency of ultrasonic treatment is 20-40 kHz, and the power is 50-100 W. The setting of parameters can effectively promote the uniform dispersion of silicon carbide particles in the modified silicon carbide solution and avoid precipitation and agglomeration. In addition, ultrasound can accelerate chemical reactions, increase reaction rates, and thus speed up the preparation process. Ultrasonic treatment can optimize the dispersibility of the solution without damaging the paper base, and improve the stability, heat resistance and durability of the coating.

[0047] Preferably, in step S300, the protective coating is an epoxy resin coating, which contains 20-30wt% of polyamide, 8-10wt% of sodium carboxymethyl cellulose and 6-8wt% of nylon; polyamide has good adhesion and abrasion resistance, which helps to enhance the durability of the coating; sodium carboxymethyl cellulose can improve the fluidity and uniformity of the coating, ensuring that the coating forms a tight protective film on the paper surface; nylon improves the toughness and UV resistance of the coating, avoiding fading and damage of the coating during long-term use. In general, the protective coating can effectively improve the durability, oxidation resistance and environmental corrosion resistance of the tipping paper, extend its service life and ensure the stability of the packaging material in different environments.

[0048] Further, the preparation method of the epoxy resin coating adopts the following steps:

[0049] S311, heating the epoxy resin to 60-80°C, stirring until uniform, and sequentially adding polyamide and nylon powder to obtain a mixed solution; dissolving sodium carboxymethyl cellulose in deionized water to obtain a sodium carboxymethyl cellulose solution;

[0050] S312, slowly add the sodium carboxymethyl cellulose solution into the mixed solution, continue stirring until it is uniform, and perform defoaming treatment to obtain the epoxy resin coating.

[0051] Preferably, the viscosity of the epoxy resin coating is between 100 and 500 cP, which helps the coating to form a uniform and smooth protective layer on the surface of the tipping paper, ensures good adhesion and durability of the coating, and improves the overall performance and stability of the tipping paper; moderate viscosity can ensure that the coating has moderate fluidity during the coating process and avoid unevenness or sagging.

[0052] Preferably, the thickness of the substrate layer is between 50 and 150 μm; the thickness of the modified silicon carbide layer is between 1 and 5 μm; the thickness of the protective layer is between 8 and 20 μm. The thickness of the substrate layer ensures that the tipping paper has sufficient mechanical strength and stability to withstand external pressure and wear during use; the thickness of the modified silicon carbide layer can effectively reduce the migration of heavy metals, while enhancing the chemical stability and thermal stability of the tipping paper, thereby improving its ability to protect against harmful substances without affecting the flexibility of the paper; the thickness of the protective layer can provide additional protection, enhance the resistance of the tipping paper to the external environment, and improve its durability and service life.

[0053] Embodiment 1:

[0054] This embodiment provides a low heavy metal content plugging paper and a preparation method thereof, wherein the plugging paper comprises a base material layer, a modified silicon carbide layer, and a protective layer arranged from the inside to the outside; the preparation method comprises:

[0055] S100, washing the cellulose paper substrate with deionized water by immersion, plasma-treating the substrate with nitrogen, and drying the substrate with hot air to complete pretreatment and obtain a paper substrate;

[0056] S200, performing ultrasonic treatment at a frequency of 30 kHz and a power of 70 W, immersing the paper base in the modified silicon carbide layer solution to obtain a tipping paper containing a modified silicon carbide layer;

[0057] S300, coating the epoxy resin coating on the surface of the plugging paper containing the modified titanium carbide layer to obtain the plugging paper with low heavy metal content;

[0058] Wherein, the modified silicon carbide solution is N-doped carbon quantum dots-silicon carbide, and the following steps are adopted:

[0059] S211, dissolving lignin and urea in a mass ratio of 1:0.08 in deionized water to obtain a first mixed solution;

[0060] S212, placing the first mixed solution into a reactor, heating the reaction at a temperature of 200° C. for 6 hours, and cooling to room temperature to obtain an N-doped carbon quantum dot solution;

[0061] S213, adding silicon carbide powder with a mass ratio of 1:2 to the N-doped carbon quantum dot solution, performing heat treatment at a temperature of 1400° C. in a nitrogen atmosphere, and cooling to room temperature to obtain an N-doped carbon quantum dot-silicon carbide composite material;

[0062] S214, dissolving the N-doped carbon quantum dot-silicon carbide composite material in anhydrous ethanol to obtain a modified silicon carbide solution

[0063] S215, adding 1.5% polyvinyl alcohol to the modified silicon carbide solution;

[0064] The protective coating is an epoxy resin coating, which contains 25wt% polyamide, 9wt% sodium carboxymethyl cellulose and 7wt% nylon, and adopts the following steps:

[0065] S311, heating the epoxy resin to 70° C., stirring until uniform, and sequentially adding polyamide and nylon powder to obtain a mixed solution; dissolving sodium carboxymethyl cellulose in deionized water to obtain a sodium carboxymethyl cellulose solution;

[0066] S312, slowly add the sodium carboxymethyl cellulose solution into the mixed solution, continue stirring until it is uniform, and perform defoaming treatment to obtain the epoxy resin coating, and adjust the viscosity to 300 cP.

[0067] Embodiment 2:

[0068] This embodiment provides a low heavy metal content plugging paper and a preparation method thereof, wherein the plugging paper comprises a base material layer, a modified silicon carbide layer, and a protective layer arranged from the inside to the outside; the preparation method comprises:

[0069] S100, washing the cellulose paper substrate with deionized water by immersion, plasma-treating the substrate with nitrogen, and drying the substrate with hot air to complete pretreatment and obtain a paper substrate;

[0070] S200, performing ultrasonic treatment at a frequency of 20 kHz and a power of 50 W, immersing the paper base in the modified silicon carbide layer solution to obtain a tipping paper containing a modified silicon carbide layer;

[0071] S300, coating the epoxy resin coating on the surface of the plugging paper containing the modified titanium carbide layer to obtain the plugging paper with low heavy metal content;

[0072] Wherein, the modified silicon carbide solution is N-doped carbon quantum dots-silicon carbide, and the following steps are adopted:

[0073] S211, dissolving lignin and urea in a mass ratio of 1:0.05 in deionized water to obtain a first mixed solution;

[0074] S212, placing the first mixed solution into a reactor, heating the reaction at a temperature of 180° C. for 8 h, and cooling to room temperature to obtain an N-doped carbon quantum dot solution;

[0075] S213, adding silicon carbide powder with a mass ratio of 1:1 to the N-doped carbon quantum dot solution, performing heat treatment at a temperature of 1000° C. in a nitrogen atmosphere, and cooling to room temperature to obtain an N-doped carbon quantum dot-silicon carbide composite material;

[0076] S214, dissolving the N-doped carbon quantum dot-silicon carbide composite material in anhydrous ethanol to obtain a modified silicon carbide solution

[0077] S215, adding 0.5% polyvinyl alcohol to the modified silicon carbide solution;

[0078] The protective coating is an epoxy resin coating, which contains 20wt% polyamide, 8wt% sodium carboxymethyl cellulose and 6wt% nylon, and adopts the following steps:

[0079] S311, heating the epoxy resin to 60° C., stirring until uniform, and sequentially adding polyamide and nylon powder to obtain a mixed solution; dissolving sodium carboxymethyl cellulose in deionized water to obtain a sodium carboxymethyl cellulose solution;

[0080] S312, slowly add the sodium carboxymethyl cellulose solution into the mixed solution, continue stirring until it is uniform, and perform defoaming treatment to obtain the epoxy resin coating, and adjust the viscosity to 500 cP.

[0081] Embodiment 3:

[0082] This embodiment provides a low heavy metal content tipping paper and a preparation method thereof, the steps are as follows:

[0083] This embodiment provides a low heavy metal content plugging paper and a preparation method thereof, wherein the plugging paper comprises a base material layer, a modified silicon carbide layer, and a protective layer arranged from the inside to the outside; the preparation method comprises:

[0084] S100, washing the cellulose paper substrate with deionized water by immersion, plasma-treating the substrate with nitrogen, and drying the substrate with hot air to complete pretreatment and obtain a paper substrate;

[0085] S200, performing ultrasonic treatment at a frequency of 40 kHz and a power of 100 W, immersing the paper base in the modified silicon carbide layer solution to obtain a tipping paper containing a modified silicon carbide layer;

[0086] S300, coating the epoxy resin coating on the surface of the plugging paper containing the modified titanium carbide layer to obtain the plugging paper with low heavy metal content;

[0087] Wherein, the modified silicon carbide solution is N-doped carbon quantum dots-silicon carbide, and the following steps are adopted:

[0088] S211, dissolving lignin and urea in a mass ratio of 1:0.1 in deionized water to obtain a first mixed solution;

[0089] S212, placing the first mixed solution into a reactor, heating the reaction at a temperature of 250° C. for 6 hours, and cooling to room temperature to obtain an N-doped carbon quantum dot solution;

[0090] S213, adding silicon carbide powder with a mass ratio of 1:3 to the N-doped carbon quantum dot solution, performing heat treatment at a temperature of 1600° C. in a nitrogen atmosphere, and cooling to room temperature to obtain an N-doped carbon quantum dot-silicon carbide composite material;

[0091] S214, dissolving the N-doped carbon quantum dot-silicon carbide composite material in anhydrous ethanol to obtain a modified silicon carbide solution

[0092] S215, adding 3% polyvinyl alcohol to the modified silicon carbide solution;

[0093] The protective coating is an epoxy resin coating, which contains 30wt% of polyamide, 10wt% of sodium carboxymethyl cellulose and 8wt% of nylon, and adopts the following steps:

[0094] S311, heating the epoxy resin to 60° C., stirring until uniform, and sequentially adding polyamide and nylon powder to obtain a mixed solution; dissolving sodium carboxymethyl cellulose in deionized water to obtain a sodium carboxymethyl cellulose solution;

[0095] S312, slowly add the sodium carboxymethyl cellulose solution into the mixed solution, continue stirring until it is uniform, and perform defoaming treatment to obtain the epoxy resin coating, and adjust the viscosity to 100 cP.

[0096] Comparative Example 1:

[0097] This comparative example provides a tipping paper which is purchased from outside.

[0098] Performance Testing:

[0099] (1) High temperature resistance test: The tipping paper samples of Examples 1-3 and Comparative Example 1 were cut into uniform 50 mm × 50 mm pieces, placed in a high temperature oven at 200° C. for 3 h, and observed and recorded. The results are shown in Table 1.

[0100] (2) Adhesion test: The tipping papers of Examples 1-3 and Comparative Example 1 were attached to the coating surface by means of adhesive tape, and then the adhesive tape was quickly torn off to check whether the coating was peeled off. The results are shown in Table 1.

[0101] (3) Thickness test: The thickness of each layer of the release paper samples of Examples 1-3 and Comparative Examples 1-2 was measured. The results are shown in Table 1.

[0102] Table 1

[0103] project Example 1 Example 2 Example 3 Comparative Example 1 200℃2h condition intact intact intact Discoloration Adhesion test No peeling No peeling No peeling Slight peeling Base material layer 100μm 50μm 150μm / Modified silicon carbide layer 3μm 5μm 1μm / Protective layer 12μm 20μm 8μm /

[0104] By comparing and analyzing Examples 1-3 with Comparative Example 1, the samples in the Examples all remained intact under high temperature conditions, while Comparative Example 1 changed color, showing poor thermal stability. In addition, the adhesion of all Examples was free of peeling, showing good adhesion performance, while Comparative Example 1 had slight peeling and weak adhesion. In summary, the tipping paper of the present application is superior to Comparative Example 1 in terms of thermal stability and adhesion, and has better performance.

[0105] Finally, it should be noted that the embodiments of the present disclosure have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes are obvious to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The choice of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. A method for preparing a tipping paper with low heavy metal content, characterized in that: The tipping paper comprises a base material layer, a modified silicon carbide layer, and a protective layer arranged from the inside to the outside; the preparation method comprises: S100, pretreating a cellulose paper substrate to obtain a paper base; S200, soaking the paper base in a modified silicon carbide layer solution under ultrasonic treatment to obtain a tipping paper containing a modified silicon carbide layer; S300, coating the protective coating on the surface of the plugging paper containing the modified titanium carbide layer to obtain the plugging paper with low heavy metal content; Wherein, the modified silicon carbide solution is N-doped carbon quantum dot-silicon carbide.

2. The preparation method according to claim 1, characterized in that: In step S200, the modified silicon carbide solution adopts the following steps: S211, dissolving lignin and urea in deionized water to obtain a first mixed solution; S212, placing the first mixed solution into a reactor, heating the reaction at a temperature of 180 to 250° C. for 4 to 8 hours, and cooling to room temperature to obtain an N-doped carbon quantum dot solution; S213, adding silicon carbide powder to the N-doped carbon quantum dot solution, performing heat treatment under a nitrogen atmosphere, and cooling to room temperature to obtain an N-doped carbon quantum dot-silicon carbide composite material; S214, dissolving the N-doped carbon quantum dot-silicon carbide composite material in anhydrous ethanol to obtain the modified silicon carbide solution.

3. The preparation method according to claim 2, characterized in that: In step S211, the mass ratio of the lignin to the urea is 1:(0.05-0.1); and / or In step S213, the mass ratio of the silicon carbide powder to the N-doped carbon quantum dot solution is 1:(1-3); and / or In step S213, the temperature of the heat treatment is between 1000 and 1600°C.

4. The preparation method according to claim 2, characterized in that: After step S214, the method further includes: S215, adding a dispersant to the modified silicon carbide solution; The mass of the dispersant accounts for 0.5-3% of the mass of the modified silicon carbide, and the dispersant includes at least one of polyvinyl alcohol and sodium polyacrylate.

5. The preparation method according to claim 1, characterized in that: In step S100, the pretreatment includes cleaning treatment, surface modification treatment and drying treatment.

6. The preparation method according to claim 1, characterized in that: In step S200, The frequency of the ultrasonic treatment is 20-40kHz, and the power is 50-100W.

7. The preparation method according to claim 1, characterized in that: In the step S300, the protective coating is an epoxy resin coating, and the epoxy resin coating contains 20-30 wt% of polyamide, 8-10 wt% of sodium carboxymethyl cellulose and 6-8 wt% of nylon.

8. The preparation method according to claim 7, characterized in that: The viscosity of the epoxy resin coating is between 100 and 500 cP.

9. The preparation method according to claim 1, characterized in that: The thickness of the substrate layer is between 50 and 150 μm; The thickness of the modified silicon carbide layer is between 1 and 5 μm; The thickness of the protective layer is between 8 and 20 μm.

10. A tipping paper with low heavy metal content, characterized in that: The low heavy metal content tipping paper is prepared by the preparation method according to any one of claims 1 to 9.